Material interfaces. Biological meets digital - Sabrina Lucibello; Lorena Trebbi; Chiara Del Gesso (Agathón)
The introduction to the concept of ‘digital materiality’ goes beyond the custom of considering matters’ physical characteristics as the opposite of virtual, binary and digital ones. Bonsiepe, in 1995, had already integrated the material characteristics of objects and the semiotic value of the interface, acknowledging its ability to become a ‘non-verbal language’, ‘spatial system’ establishing new relationships between the human body and technology. Therefore, surfaces have the key role of ‘membranes’, creating and receiving stimuli from inside and outside, and from subject and object. From this framework, it emerges the need to experiment alternative solutions meeting circularity/sustainability and experience/enjoyment needs, for example, through material interfaces or experiments on new biofabricated materials, such as microbial nanocellulose.